Insulin refill adherence among type 2 diabetes mellitus patients attending public health clinics in Perlis, Malaysia - PP, Soo; MSA, Kassim; NNA, Fazeli Shah; N, Mohmmad; YH, Ng (Penerbit Universiti Kebangsaan Malaysia, 2023)
Poor adherence to diabetes medications, particularly insulin, is still a concern. This study aimed to assess insulin refill adherence among diabetes patients attending public health clinics in Perlis before and during the COVID-19 pandemic. The underlying factors associated with insulin refill adherence were also investigated. This cross-sectional study was conducted among type 2 diabetes mellitus patients with insulin therapy from five primary health clinics in Perlis. Simple random sampling method was used to select participants from the Pharmacy Information System (PhIS) database. Adherence to insulin refill was measured by medication possession ratio before and during the COVID-19 pandemic. A general linear model was used to identify factors associated with adherence to insulin refills. A total of 426 patients were included in this study. Patients in this study were mostly Malay (94.3%) and female (63.1%). The insulin refill adherence was significantly poorer during the COVID-19 pandemic (mean=59.24, SD=28.97) than before the pandemic (mean=68.31, SD=31.27) (p<0.001). Only total daily insulin dose (adjusted β = -0.129; p=0.012) and not having hypertension (adjusted β = -7.359; p=0.043) were significantly associated with insulin refill adherence. This study highlighted that overall insulin refill adherence among patients in public health clinics in Perlis was still low, especially during the COVID-19 pandemic. Special attention should be given to patients using high total daily insulin doses and having no hypertension to improve adherence.